Kyai Leadership in the Development of Ecological System Theory in Islamic Boarding Schools - Masruhin, Salis; Isma, Asad; Badarussyamsi, Badarussyamsi (Al-Miskawaih: Journal of Science Education, 2023)
This article reveals why Kyai's charismatic leadership is the most important supporting element in the development of ecological systems theory and not an obstacle to the progress of Islamic boarding schools. This article comes from qualitative research which collects data through observation, interviews and documentation. The research results show that Kyai leadership in developing ecological systems theory in Islamic boarding schools is carried out with a charismatic type and a collective-collegial pattern, which is applied to the typical qualifications of Islamic boarding school leaders and their educational methodology. In the EST perspective, Islamic boarding schools are able to provide education in an integrated, comprehensive (holistic) and total manner. It is called integrative because in Islamic boarding school education, educational domains such as school, family and society are integrated into one unified whole. Comprehensive because Islamic boarding schools educate all human qualities, both cognitive-intellectual, mental-emotional, and moral-spiritual. Artikel ini mengungkap mengapa kepemimpinan kharismatik Kyai menjadi unsur pendukung terpenting dalam pengembangan teori sistem ekologi dan bukan menjadi penghambat kemajuan pesantren. Artikel ini berasal dari penelitian kualitatif yang mengumpulkan data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menyebutkan bahwa kepemimpinan Kyai dalam pengembangan teori sistem ekologi di pesantren dilaksanakan dengan tipe karismatik dan pola kolektif-kolegial, yang diterapkan pada kualifikasi tipikal pemimpin pesantren dan metodologi pendidikannya. Dalam perspektif EST, pesantren mampu menyelenggarakan pendidikan secara terpadu, komprehensif (holistik), dan total. Disebut integratif karena dalam pendidikan pesantren, domain pendidikan seperti sekolah, keluarga, dan masyarakat diintegrasikan menjadi satu kesatuan yang utuh. Komprehensif karena pesantren mendidik seluruh kualitas manusia, baik kognitif-intelektual, mental-emosional, dan moral-spiritual.